THE ACTION OF OIL, GAS CONDENSATE, DRILLING CUTTINGS AND DRILLING MUD ON THE BIOTA OF THE CASPIAN SEA - A. S. Abdusamadov; A. P. Panarin; G. S. Gorbunova; L. D. Kovalenko; B. R. Guseinova; N. V. Panarina; A. M. Dokhtukaeva; L. A. Dudurkhanova (Юг России: экология, развитие, 2014)
Conducted experimental studies on the effect of crude oil, gas condensate, drilling muds and cuttings on the zooplankton, on the plant pigments of phytoplankton, on the saprophytic microflora, as well as on representatives of ichthyofauna of the Caspian sea.